Role of health information technology in enhancing chronic disease management: a scoping review protocol - Szu-Han Wang; Yen-Liang Lee; Emily Chia-Yu Su; Chia-Hsuan Tsai (BMJ Open)
Introduction Chronic diseases, such as diabetes, hypertension and cardiovascular diseases, represent a significant burden on global health systems. Health information technology (HIT) offers innovative solutions to improve disease management, patient outcomes and healthcare efficiency. However, the diverse applications and impacts of HIT in chronic disease management are not well understood. The objective of this scoping review is to assess the extent and type of evidence on the role of HIT in enhancing chronic disease management.Methods and analysis This protocol outlines a scoping review to assess the extent and nature of the evidence on the role of HIT in managing chronic diseases. The review will be conducted in accordance with the JBI methodology for scoping reviews. This review will include studies involving adult patients with chronic diseases. The focus will be on various HIT interventions, including electronic health records (EHRs), telehealth services, mobile health (mHealth) applications, remote monitoring devices and health information exchanges (HIEs). Studies conducted in primary care, hospital and community health settings will be considered. Exclusions will include studies focused on paediatric populations or non-digital health interventions. We will include quantitative, qualitative and mixed-methods studies published from January 2013 to December 2024. A comprehensive search will be conducted across PubMed, Cumulative Index of Nursing and Allied Health Literature (CINAHL), Scopus and Google Scholar. Reference lists of included studies will be screened for additional sources. Two independent reviewers will screen titles, abstracts and full texts, extract data and resolve discrepancies through discussion or consultation with a third reviewer. The study is scheduled to begin in May 2025 and conclude by November 2025, and the process will be documented in a Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow diagram. The data will be presented as tables, charts and a narrative summary.Ethics and dissemination As this review involves the analysis of publicly available literature, ethical approval is not required. The results will be disseminated via peer-reviewed publications, conference presentations and engagements with stakeholders involved in chronic disease care and digital health policy. The authors will also explore opportunities to share supplementary materials in open-access repositories to promote transparency and reproducibility.